FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KUALITAS KINERJA PEGAWAI DI KANTOR KELURAHAN MACORAWALIE KECAMATAN PANCARIJANG - A, Nurul Muhliza; Adnan, Andi Astinah; Mannu, Ahmad (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study aims to examine what factors affect the quality of employee performance in the macorawalie village office. The type of research used in this research is a quantitative approach. The population of this study was 87 people. The questionnaire is a data collection technique used with data analysis techniques, namely IBM SPSS Statistics 26. based on the results of variable recapitulation of internal factors and external factors with a percentage of 71.75%% in the good category and variable recapitulation of employee performance quality with a result of 75.2% in the expected good category. In addition, the factors that affect the quality of employee performance in the macorawalie village office, Pancarijang sub-district are